Prevalence of Low Vitamin B12 Status among Type-2 Diabetic Patients on Long-Term Metformin and its Effect on Neuropathy Scores - Muntingh, George L. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.